2013
DOI: 10.1126/science.1243110
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cytoplasmic Volume Are Sufficient to Drive Spindle Scaling

Abstract: The mitotic spindle must function in cell types that vary greatly in size, and its dimensions scale with the rapid, reductive cell divisions that accompany early stages of development. The mechanism responsible for this scaling is unclear, because uncoupling cell size from a developmental or cellular context has proven experimentally challenging. Here we combined microfluidic technology with Xenopus egg extracts to characterize spindle assembly within discrete, geometrically defined volumes of cytoplasm. Reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
195
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(220 citation statements)
references
References 30 publications
19
195
2
Order By: Relevance
“…Thus, the localization of SAFs by microtubules is sufficient to explain the observation that spindles assemble outside the peak of the Ran gradient in MUG cells. It has previously been shown that the size of the spindle is correlated with cell size during changes in early development (36)(37)(38)(39), between different species (39,40), between genetically different individuals within a species (40), and when spindles are assembled in vitro in cell extracts encapsulated in droplets (41,42). To our knowledge, the scaling of the spindle with cell size has not been investigated in human tissue culture cells such as were used in this study.…”
Section: Resultsmentioning
confidence: 92%
“…Thus, the localization of SAFs by microtubules is sufficient to explain the observation that spindles assemble outside the peak of the Ran gradient in MUG cells. It has previously been shown that the size of the spindle is correlated with cell size during changes in early development (36)(37)(38)(39), between different species (39,40), between genetically different individuals within a species (40), and when spindles are assembled in vitro in cell extracts encapsulated in droplets (41,42). To our knowledge, the scaling of the spindle with cell size has not been investigated in human tissue culture cells such as were used in this study.…”
Section: Resultsmentioning
confidence: 92%
“…Most intriguingly, the spindle size scales linearly with the cell size up to a certain limit; and such a biphasic scaling relationship, as well as the critical cell size and spindle size for the biphasic transition, appear surprisingly consistent across metazoan species (5,8,10). Such size scaling is also partially reproduced in in vitro spindle reconstitution experiments (15,16). From the physics point of view, such universal size-scaling phenomena are highly significant, as they suggest intrinsic principles in the spatial organization of the mitotic spindle.…”
Section: Introductionmentioning
confidence: 77%
“…Remarkably, only duplicates related to cytoskeleton organization were retained under strong positive selection after both the a-and m-WGD events. With increased cell volume being one of the few constant alterations induced by polyploidy (Ramsey and Schemske, 2002), to what extent adaptive diversification of cytoskeleton genes may support the necessary scaling of intracellular structures after WGDs should be further examined (Hazel et al, 2013). The vast majority of retained duplicates in B. laevigata presented evidence of purifying selection, matching the hypothesis that dosage effects are crucial in maintaining functional traits after WGDs (Birchler and Veitia, 2012).…”
Section: Biased Genome Fractionation Over Timementioning
confidence: 86%